Driving Safety Education at Sewon Muhammadiyah Middle School, Bantul, Daerah Istimewa Yogyakarta: Edukasi Keselamatan Berkendaraan di SMP Muhammadiyah Sewon, Bantul, Daerah Istimewa Yogyakarta - Anita Rahmawati; Sri atmaja P. Rosyidi; Hakas Prayuda; Taufiq I. Maulana (Universitas Lancang Kuning, 2023)
Education about the importance of road safety is a way to shape children mindset and character, especially adolescence who have the potential to actively traffic on the road. Equipping them with knowledge and raising awareness of traffic rules in teenagers is expected to be able to help give them the best chance of keeping safe while they’re young and as they get older -become obeying people and pioneers of road safety. This service activity is a concrete step to create young people awareness about the importance of road and driving safety. Driving safety education at Sewon Muhammadiyah Middle School, Bantul becomes an effort to provide knowledge readiness for pre-teenagers (under 16 years) so that it is hoped that they will be scientifically and mentally ready to drive at the age of 17 and over (after they get a driver's license/SIM). From this community service activity, the results showed an increase in understanding related to driving safety for adolescence, especially children in grade 2 junior high school at Sewon Muhammadiyah Middle School, as indicated by the average pre-test results that answered correctly at 48.18% and post-test results that answered correctly at 81. 90%. There was an increase in understanding of safety education participants by 33.72%.